Stabilitas Emulsi Minuman Virgin Coconut Oil dengan Pelarut Air Kelapa - Nur Mu’min; Rizka Oktavia (Politeknik Negeri Cilacap, 2021)
Virgin Coconut Oil (VCO) is a pure coconut oil product whose manufacturing process does not involve the heating process and the workmanship is very simple. VCO is reportedly able to prevent and treat various diseases such as being able to kill viruses, bacteria, increase endurance and moisturize the skin so that people are increasingly interested in consuming it, but its